PERLINDUNGAN DINI PERILAKU BULLYING/PERUNDUNGAN ANTAR ANAK DI SEKOLAH - Anjari, Warih Anjari; Batjo, Siti Ristyani Putri; Kholifah, Nur; Saidah, Andi (Universitas 17 Agustus 1945 Jakarta, 2025)
Violence against children in Indonesia has increased significantly. Data on the number of sexual violence cases from the Ministry of PPA shows that the number of victims of violence against children is increasing continuously from 2020 - 2023. This takes the form of physical, sexual violence, emotional abuse or neglect of children. The impact of violence on children is very detrimental to children's development, both physically and psychologically. One of the triggers for increasing violence against children is easy access to information through digital media. In the era of digitalization, children get information easily, by using cellphone communication facilities. This service was carried out for students at SDN Ciketing Udik 3 Bantar Gebang, Bekasi City to strengthen their understanding of forms of bullying violence, especially among children at school. The method is by means of presentation, discussion/consultation, and pre-test & post-test. The result of this activity was an increase in the aspects of knowledge, understanding and application of bullying among students at SDN Ciketing Udik 3. Bantar Gebang, Bekasi City. However, aspects of understanding and implementing bullying still need to be improved to prevent them from becoming victims of bullying. Keywords: protection, violence between children, bullying at school